The role of tax literacy on MSME tax compliance: The mediating effect of public trust and the moderating role of Kalosara - Rika, Abdul Rachman; Hasanudin, Agus Ismaya; Lestari, Tri; Retnowati, Wulan (Jurnal Akuntansi dan Auditing Indonesia, 2026)
This study aims to analyze the influence of Tax Literacy on Tax Compliance through Trust in Tax Authorities and examine the moderating role of Kalosara-based Tax Culture in MSMEs. The research method uses a quantitative approach with a survey design of 300 MSMEs selected using purposive sampling. Data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) to test direct, indirect, and moderating relationships between variables. The results of the study indicate that tax literacy has no direct effect on tax compliance, but significantly influences trust in tax authorities, which in turn positively influences tax compliance. Trust is proven to fully mediate this relationship, while Kalosara-based tax culture does not act as a moderating variable. These findings suggest that tax compliance is more determined by institutional factors than cognitive and cultural factors. The implication is that increasing compliance needs to be focused on strengthening trust in the tax authorities. The novelty of this research lies in the integration of Social Capital Theory in the context of Kalosara culture in the MSME tax compliance model.